Comparison of Biuret and soybean meal for wintering cows on bluestem pasture - H.A. Thyfault; E.F. Smith; L.H. Harbers (Kansas Agricultural Experiment Station Research Reports, 1970)
Biuret, a non protein nitrogen compound, has shown promise as a protein substitute for ruminants fed poor quality roughages. Urea, by comparison, cannot be sued without an adequate supply of energy in the form of either grain or molasses. Biuret is not broken down to ammonia so rapidly as urea is. Biuret, therefore, is less toxic than urea.
Keywords: Cattlemen& #x27; s Day; 1970; Report of progress (Kansas State University. Agricultural Experiment Station); 536; Beef; Biuret; Soybean meal; Bluestem pasture